2020
DOI: 10.1038/s41467-020-17837-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of light-responsive protein binding in the monobody non-immunoglobulin scaffold

Abstract: Monobodies are synthetic non-immunoglobulin customizable protein binders invaluable to basic and applied research, and of considerable potential as future therapeutics and diagnostic tools. The ability to reversibly control their binding activity to their targets on demand would significantly expand their applications in biotechnology, medicine, and research. Here we present, as proof-of-principle, the development of a light-controlled monobody (OptoMB) that works in vitro and in cells and whose affinity for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…(E) Encoding of the LOV domain enables intracellular control of protein location and immunopurification. 11 , 13 Adapted with permission from refs ( 10 , 12 , 13 , and 22 ). Copyright 2020 Wiley-VCH, and 2019 and 2020 Springer Nature.…”
Section: Light Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…(E) Encoding of the LOV domain enables intracellular control of protein location and immunopurification. 11 , 13 Adapted with permission from refs ( 10 , 12 , 13 , and 22 ). Copyright 2020 Wiley-VCH, and 2019 and 2020 Springer Nature.…”
Section: Light Activationmentioning
confidence: 99%
“…Harnessing the power of a natural protein switch, Avalos and Toettcher groups have jointly created antibody mimetics dubbed “optobinders” ( Figure 2 E). 13 The basis for their design is the insertion of a light-oxygen-voltage domain from Avena sativa phototropin 1 (AsLOV2) into the structure of nanobodies (OptoNBs) 11 and monobodies (OptoMBs). 13 The AsLOV2 domain exerts switching under blue light (447 nm) via a large conformational change triggered by the covalent conjugation of photoexcited flavin chromophore FMN to a conserved cysteine.…”
Section: Light Activationmentioning
confidence: 99%
“…Recently, nanobodies have been controlled by light following three strategies: (i) the As LOV2 domain (or, more precisely, an optimized version of it called sLOV) was inserted into a surface-exposed loop of the nanobody following a previously reported method ( 45 ) whereby the blue light-triggered unfolding of the Jα helix brings about a local conformational change, which, in turn, results in either loss or gain of binding capacity by the nanobody towards its antigen ( 72 ). The same method was shown to work also with monobodies ( 73 ), which are synthetic customizable protein binders constructed using a fibronectin type III domain as molecular scaffold; (ii) the localization of the nanobody was controlled by a light-inducible heterodimerizing pair ( 74 ); (iii) the nanobody was split into two fragments, which were brought into physical proximity using a light-inducible heterodimerizer ( 75 ). Importantly, optonanobodies offer the opportunity to control the localization of selected endogenous proteins, as long as nanobodies specific for them can be developed ( Fig.…”
Section: Ways To Control Protein Function With Lightmentioning
confidence: 99%
“…1G ). This method was recently used by the Niopek group to create a light-inducible version of the Cas9 inhibitor AcrIIA4 ( 132 ) and by the Avalos and Toettcher groups to obtain optonanobodies and monobodies ( 72 , 73 ). Interestingly, the authors found variants whereby the As LOV2 domain disrupted the binding of the nanobody to its target in the dark rather than in the lit state ( 72 ).…”
Section: Ways To Control Protein Function With Lightmentioning
confidence: 99%
“…
either based on split nanobodies (optobody) [7] or hybrid proteins that utilize a photosensitive switch (OptoNB and OptoMB) [8,9] or circularly permuted bacterial dihydrofolate reductase (LAMA). [10] Nonetheless, these engineered intrabodies exhibit a relatively slow activation kinetics or suffer from a relatively low or modest dynamic range of light-induced changes.Bearing these unmet needs in mind, we introduce herein a set of smart monobodies and nanobodies that respond to light within seconds, in the form of ON-switches (sunbody) or OFF-switches (moonbody).
…”
mentioning
confidence: 99%